Contemporary outcomes of catheter ablation of the structural ventricular tachycardias in severe ischemic and non‐ischemic cardiomyopathies in Turkish population - Emir Baskovski; Timucin Altin; Omer Akyurek; Mahmut Ekrem Cunetoglu; Volkan Kozluca; Irem Muge Akbulut; Nail Burak Ozbeyaz; Nazli Turan Serifler; Eralp Tutar (Journal of Arrhythmia, 2024)
Abstract Introduction Currently, there are no data regarding outcomes of the catheter ablation for structural ventricular tachycardia (VT) in Türkiye. In this observational study, we aim to investigate cardiac outcomes of patients undergoing catheter VT ablation at a tertiary center in Türkiye. Methods This was a retrospective observational study performed at a single university center. Patients with a confirmed ischemic or non‐ischemic cardiomyopathy, undergoing structural VT ablation were included. Procedural and mid‐term outcomes were analyzed. Results A total of 124 patients were enrolled in the study. 54(43.5%) patients presented with an electrical storm. During the mean follow‐up of 351 ± 232 days 10(8.1%) patients experienced a recurrence. There was only one peri‐procedural death and cardiac tamponade occurred in two patients.14(11.3%) patients died during the follow‐up, most commonly due to a cardiovascular death. In the multivariate analysis only age >70 was found to be correlated with death during follow‐up, with p =.008, HR = 4.923. Conclusion A good acute success with low complications was observed in patients undergoing VT ablation for structural heart disease in a tertiary center in Türkiye. Mid‐term outcomes are comparable with international studies with no difference in VT recurrence in ischemic and non‐ischemic patients. Similar to international studies, significant mid‐term mortality was observed.